Progeroid Syndrome of De Barsy With Hypocalcemic Seizures - Cheriathu, J; D'souza, IE; John, LJ; El Bahtimi, R (Journal of Nepal Paediatric Society, 2012)
De Barsy et al first reported a rare cutaneo-oculo-cerebral malformation-syndrome now commonly referred as ‘progerioid syndrome of de Barsy’. It is the constellation of progeria-like appearance, cutis laxa, intrauterine growth retardation, corneal clouding and hypotonia. We report a case of Debarsy syndrome in a neonate presented at birth with typical clinical features with hypocalcemic seizures. There are no previous reports among Afghani origin and also first case reported from United Arab Emirates, there have been no reported cases of hypocalcemic seizures. J Nepal Paediatr Soc 2012;32(2):175-177 doi: http://dx.doi.org/10.3126/jnps.v32i2.5993